Exploring the Role of Online Social Capital in Differentiating Technology Addiction Effect on Well-Being - Mirko Duradoni; Giulia Colombini; Virginia Battistoni; Veronica Zagaglia; Andrea Guazzini (Human Behavior and Emerging Technologies)
Today’s widespread and increasing access to the Internet and new technologies not only offers great opportunities but also risks for problematic use, whose psychological dynamics need to be understood in depth. This study examines how technology addiction may differentially affect well-being (i.e., psychological, eudaimonic, and cognitive hedonic) and digital life balance depending on people’s reported levels of online social capital. Seven hundred and eleven participants (75.70% female; Mage=28.33 years, SD=12.30) took part in the data collection. Drawing on the Psychology of Harmony and Harmonization framework, the study found that people with high levels of addiction and high levels of online social capital showed higher well-being scores, as indicated by higher perceptions of life satisfaction and feelings of personal and social success, compared to people with high addiction patterns and low levels of online social capital. In addition, the results also highlighted a better digital life balance in the former group. Overall, the findings point to online social capital as a key factor in unraveling the different dynamics of social media and Internet addiction, showing how it can contribute to ensuring the satisfaction of driving social needs, maintaining better well-being even in the face of maladaptive behaviors, and ultimately challenging a monolithic concept of new forms of addiction. Indeed, the results suggest the potential existence of distinct types or shades of technological addiction that impact well-being differently and reflect varying levels of psychological distress, depending on underlying social needs and behaviors.